Investigation into the telecommunication service provider industry : will the rate of new service technology adoption affect firm’s performance? - Lim, Poon Chong. (2008)
This study examines whether the rate of adoption of new technology in the mobile telecommunication service provider industry will affect a firm’s performance as measured by Tobin's q.